1980
DOI: 10.1007/bfb0088461
|View full text |Cite
|
Sign up to set email alerts
|

Generalizations of the Bernstein-Gelfand-Ponomarev reflection functors

Abstract: I nt r oduc t i onReflection functors were introduced into the representation theory of quivers by Bernstein, Gelfand and Ponomarev in their work on the 4-subspace problem and on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
203
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(206 citation statements)
references
References 12 publications
0
203
0
3
Order By: Relevance
“…Most algebraists probably became aware of the existence non-trivial derived equivalences when Happel showed that "tilting" (as introduced by Brenner and Butler [15]) leads to a derived equivalence between finite dimensional algebras [32]. This was generalized by Rickard who worked out the Morita theory for derived categories of rings [61,62].…”
Section: Some Backgroundmentioning
confidence: 99%
“…Most algebraists probably became aware of the existence non-trivial derived equivalences when Happel showed that "tilting" (as introduced by Brenner and Butler [15]) leads to a derived equivalence between finite dimensional algebras [32]. This was generalized by Rickard who worked out the Morita theory for derived categories of rings [61,62].…”
Section: Some Backgroundmentioning
confidence: 99%
“…. The now classical theory (based on homological algebra but avoiding derived categories) is due to: Brenner-Butler [14], who first proved the 'tilting theorem', Happel-Ringel [35], who improved the theorem and defined tilted algebras, Bongartz [13], who streamlined the theory, and Miyashita [55], who generalized it to tilting modules of projective dimension > 1. The use of derived categories goes back to D. Happel [31].…”
Section: First Links Between the Module Categories Now Assume That (mentioning
confidence: 99%
“…A complex T as in condition (iii) is called a tilting complex for Λ, and Γ is tilted from Λ. Tilting complexes appeared first in the form of tilting modules, as part of Brenner and Butler's [BB80] study of the reflection functors of Bernšteȋn, Gel ′ fand, and Ponomarev [BGP73]. (The word was chosen to illustrate their effect on the vectors in a root system, namely a change of basis that tilts the axes relative to the positive roots.)…”
Section: Derived Categories Of Modulesmentioning
confidence: 99%